PERBANDINGAN ISTILAH OTONAN YANG TERDAPAT DALAM AGAMA HINDU TERHADAP AGAMA-AGAMA LAIN DI INDONESIA - Komang Trisna Dewi; Ida Ayu Diah Larashanti; Kadek Dwi Sentana Putra (Guna Widya: Jurnal Pendidikan Hindu, 2023)
Religions in the world and in Indonesia which are included in the largest religions because of the number of adherents, are Christianity, Islam, Hinduism, Buddhism, and Confucianism. This study focuses on one of the yadnya ceremonies contained in Hinduism known as Otonan where the researchers will observe and compare what terms are used by other religions in commemorating the birth day that is believed to be. This research is a qualitative research. Collecting data in this study using the method of observation and literature study. The data of this study were analyzed using a qualitative descriptive technique. The results of the research are presented in a descriptive or narrative form that is creative and in-depth. The results of the study are as follows: In Hinduism, this Otonan has the meaning of Birthday based on the Wuku Balinese Calendar. With the term Otonan, Hindus carry out a ceremony to commemorate the birthday of their people. In Christianity, the day of the Holy Spirit is celebrated every Sunday as a celebration of the resurrection of Jesus Christ from the dead. In Catholic teaching, the term otonan in Hinduism can be equated with the Selapanan ceremony. In Islamic teachings, the term is equated with the birthday of the Prophet's Birthday. The moment of someone's birth is one of the most awaited moments. Moreover, that moment was the birth of a great human being. In Buddhism, the term otonan can be equated with Vesak Day as a commemoration of the birth, enlightenment, and death of the Buddha, Siddharta Gautama. In the teachings of Confucianism, there are no celebrations that have the same purpose as the term otonan found in Hinduism.